2018
DOI: 10.1093/ntr/nty089
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Urinary Biomarkers of Exposure in Humans Using Electronic Cigarettes, Combustible Cigarettes, and Smokeless Tobacco

Abstract: This study shows that occasional users of first generation e-cigarettes have lower levels of nicotine exposure than the users of combustible cigarettes. Compared with combustible cigarettes, e-cigarettes, and smokeless tobacco products deliver lower levels of most VOCs, with the exception of xylene, N,N-dimethylformamide, and acrylonitrile, whose metabolite levels were higher in the urine of e-cigarette users than nontobacco users. Absence of anatabine in the urine of e-cigarette users suggests that measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 44 publications
9
53
3
Order By: Relevance
“…Our findings also showed that while being exposed to high nicotine levels, long-term exclusive e-cigarette users showed significantly lower levels of toxicant biomarkers compared with cigarette smokers or dual users. These results are consistent with a number of studies examining toxicant levels in e-cigarette users in contrast to conventional tobacco users [1, 3,4,16,[18][19][20]. In line with prior studies, our findings confirm that while not without some low level risk of exposure, exclusive e-cigarette use results in lower VOC and TSNA exposure compared with use of tobacco cigarettes and dual use.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings also showed that while being exposed to high nicotine levels, long-term exclusive e-cigarette users showed significantly lower levels of toxicant biomarkers compared with cigarette smokers or dual users. These results are consistent with a number of studies examining toxicant levels in e-cigarette users in contrast to conventional tobacco users [1, 3,4,16,[18][19][20]. In line with prior studies, our findings confirm that while not without some low level risk of exposure, exclusive e-cigarette use results in lower VOC and TSNA exposure compared with use of tobacco cigarettes and dual use.…”
Section: Discussionsupporting
confidence: 93%
“…Supplementary Figure 1A depicts a schematic of the exposure protocol in benzene inhalation chambers. This adapted regimen for benzene inhalation resembles human benzene exposure levels in highly polluted gas stations, or exposure to tobacco smoke or e-cigarette vapors aerosols [12,43,44]. Under these conditions, benzene exposure had no effect in white blood cell counts in benzene exposed animals versus control animals breathing room air (Supplementary Figure 1D), while levels of the urine benzene metabolite, t,t-MA were significantly increased in benzene exposed mice (Supplementary Figure 1E).…”
Section: Benzene Exposure Induces Hyperglycemia and Hyperinsulinemia mentioning
confidence: 94%
“…All 22 included studies were published since 2015. Participant mean/ median age was infrequently reported, but the median age of those reported was 36 yr [1,8,12,23,25,26,[31][32][33][34]. Study designs were primarily cross-sectional and longitudinal studies.…”
Section: Study Sourcesmentioning
confidence: 99%
“…As a result, it is challenging to determine the amount of residual biomarkers from prior or undisclosed current cigarette smoking that contributed to a biomarker level. Importantly, few of the reviewed studies used washout periods to minimize the risk of exposure contamination (range <1 d [9,23,25,36,37] to 48 h [33]).…”
Section: 4mentioning
confidence: 99%